1986
DOI: 10.1111/j.1095-8312.1986.tb01728.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and evolution of resistance to insecticides

Abstract: The evolution of resistance to insecticides has become a serious problem world‐wide. It is important to identify patterns of insecticide use whereby insecticides can be used in integrated pest management programmes to help control insect numbers, but in such a manner that the evolution of resistance to insecticides will be retarded. The principal mechanisms of insecticide action and of resistance to these are reviewed. Some generalizations that can be made about the evolution of resistance are examined. In gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Therefore, an immediate improvement of the strategy would be to use a dose of a fast decaying insecticide that kills heterozygotes. This has already been suggested by many authors (Taylor 1986;Taylor & Georghiou 1979Curtis et al 1978;Wood & Mani 1981) and may be especially relevant in our situation: a * greatly increases when h s increases (¢gure 4).…”
Section: (D) E¡ective Dominancesupporting
confidence: 75%
“…Therefore, an immediate improvement of the strategy would be to use a dose of a fast decaying insecticide that kills heterozygotes. This has already been suggested by many authors (Taylor 1986;Taylor & Georghiou 1979Curtis et al 1978;Wood & Mani 1981) and may be especially relevant in our situation: a * greatly increases when h s increases (¢gure 4).…”
Section: (D) E¡ective Dominancesupporting
confidence: 75%
“…Other work has shown that adult female Acartia hudsonica from the same ME population are resistant to the toxic incapacitating effects of A. fundyense on feeding (Colin and Dam, 2002b). Toxin resistance in animals is mediated through different mechanisms: behavioral avoidance of toxic foods, increased rates of metabolic breakdown of toxins or decreased sensitivity to toxins (Taylor, 1986). If copepods are able to behaviorally identify and avoid toxic A. fundyense, they would either cease feeding activity when fed the alga as a sole food diet, select against the alga or, as is often observed, resume normal feeding when given a mixed diet (Colin and Dam, 2002b).…”
Section: Effects On Life History Traitsmentioning
confidence: 99%
“…Previous work with insects has found several mechanisms of evolved resistance to toxins. These mechanisms include: behavioral avoidance; metabolic resistance that increases the rate at which toxins are broken down; and decreased sensitivity to toxins (Taylor 1986). If copepods become resistant to a toxic alga via the first mechanism and develop an ability to recognize and avoid the alga, then the alga becomes a feeding deterrent.…”
Section: Feeding Deterrence or Incapacitationmentioning
confidence: 99%
“…Feeding deterrents are compounds found in algae that are detected by the grazer and cause the grazer to behaviorally cease feeding or select against that algal species (Shaw et al 1997). While these algae may contain toxic compounds, if copepods possess the ability to detect and identify a toxic compound in algae, then this is an adaptive trait that enables the grazer to avoid potentially harmful foods prior to ingesting harmful amounts (Taylor 1986). Thus, in such a case, the algae deter the feeding activity of the grazer without inducing a toxic response.…”
Section: Introductionmentioning
confidence: 99%